1999
DOI: 10.1038/sj.onc.1202482
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of the ERK and JNK mitogen-activated protein kinase cascades to Ras transformation of HT1080 fibrosarcoma and DLD-1 colon carcinoma cells

Abstract: Although an important contribution of ERK and JNK mitogen-activated protein kinase (MAPK) activation in Ras transformation of rodent ®broblasts has been determined, their role in mediating oncogenic Ras transformation of human tumor cells remains to be established. We have utilized the human HT1080 ®brosarcoma and DLD-1 colon carcinoma cell lines, which contain endogenous mutated and oncogenic N-and K-ras alleles, respectively, to address this role. Study of these cells is advantageous over Ras-transformed rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 47 publications
5
29
1
Order By: Relevance
“…Likewise, constitutively active ERK was shown to be su cient to elicit cell transformation (Greulich et al, 1996;Huang et al, 1999;Plattner et al, 1999;Verheijen et al, 1999). These ®ndings are in good agreement with our results that MEK1/ERK activation by MST4 is the underlying cause of cellular transformation induced by MST4.…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, constitutively active ERK was shown to be su cient to elicit cell transformation (Greulich et al, 1996;Huang et al, 1999;Plattner et al, 1999;Verheijen et al, 1999). These ®ndings are in good agreement with our results that MEK1/ERK activation by MST4 is the underlying cause of cellular transformation induced by MST4.…”
Section: Discussionsupporting
confidence: 82%
“…43 However, KRAS 13D appears to drive malignancy by different pathways in these cells, since HCT116 cells exhibit strong P-ERK1/2 but little or no P-PKB, whilst AZD6244-resistant DLD-1 cells exhibit modest activation of both pathways; the weak activation of ERK1/2 in DLD-1 has been reported previously. 44 This difference is even more apparent in resistant SW837 cells, which exhibit very strong P-PKB but very low activation of ERK1/2. In this context, it is perhaps relevant to think in terms of 'pathway addictionÕ as well as 'oncogene addiction'; both HCT116 cells and DLD-1 cells are addicted to KRAS 13D , 43 but only HCT116 cells exhibiting strong activation of ERK1/2 have evolved to be addicted to that pathway and are therefore sensitive to AZD6244.…”
Section: Discussionmentioning
confidence: 92%
“…There have been cumulative evidences demonstrating the proliferation-stimulating effects of PARs on fibroblasts (12), vascular endothelial cells, and smooth muscle cells in vitro (13 -18). In this minireview, we described the effects of PAR-1 or PAR-2 stimulation by the respective agonist proteinase and activating peptide on the intracellular Ca 2+ signaling and proliferation of DLD-1, a human colon carcinoma cell line (19,20). We found that PAR-1 and PAR-2 stimulation induced a similar transient [Ca 2+ ] i signal, but only PAR-2 stimulation induced cell proliferation through the activation of MEK1 / 2-ERK1 / 2.…”
Section: Introductionmentioning
confidence: 99%